Angular velocity assessment in the active straight leg raise test: Validity and reliability of an inertial device (WIMU PROTM) - José Pino-Ortega; Alejandro Hernández-Belmonte; Alejandro Bastida-Castillo; Carlos David Gómez-Carmona (Federación Extremeña de Balonmano; University of Extremadura, 2018)
Currently, there is an increase in the inertial devices application to measure active range of movement and angular velocity in exercises with a centre of rotation. Therefore, before it uses, a validity and reliability analysis of these devices are required. Objectives: The aims of this research were to describe the angular velocity performed in the active straight leg raise (EAPR) test and to assess the validity and between-units reliability of an inertial device for its measure. Method: 20 national-level football players volunteered to participate in this study, 10 youth players (age: 17.2 ± 0.87 years; height: 1.77±0.08 m; body mass: 67.96±3.4 kg; BMI: 21.7±1.2 kg/m2) y 10 senior players (age: 25.6 ± 4.24 years; height: 1.80±0.05 m; body mass: 73.35±4.2 kg; BMI: 22.63±1.7 kg/m2). 10 trials of EAPR test (5 trial with each leg) were performed. To assess between-unit's reliability, two inertial devices WIMU PROTM (RealTrack Systems, Almeria, Spain), that registered simultaneously, were compared. Instead, video analysis was used as criterion to validity assesment. The analysis and export process of inertial device data was realized by S PROTM software (RealTrack Systems, Almeria, Spain). For video-analysis, this process was realized by Kinovea®. Results: The angular velocity average performed by the athletes was 137.64±21.13º/s. A perfect validity between video analysis and WIMU PROTM (ICC=1.00; r=1.00) and a very good reliability between WIMU PROTM devices (Bias=.41º/s; CV=.22%) was found. Conclusion: WIMU PROTM is a reliable and valid device to measure angular velocity in EAPR test.